Comparative study on utilization of micro and nano sized starch particles for encapsulation of camel milk derived probiotics (Pediococcus acidolactici). (August 2019) - Ahmad, Mudasir; Gani, Adil; Hamed, Fathalla; Maqsood, Sajid
Abstract: This study investigates the efficiency of starch nano-particles in comparison with native starch for encapsulation of probiotic bacterial cells ( Pediococcus acidolactici ). Bacterial cell-death after encapsulation, viability and bioactivity retention under simulated gastro-intestinal conditions (SGID) were studied. Encapsulation in native starch showed higher viable cells (2.65 log CFU/g) ascompared to those encapsulated in starch nano-particles (1.47 log CFU/g) (P < 0.05). The characteristic peak of free cells at 1248 cm −1 indicates the presence of Pediococcus acidolactici in capsules. The micrographs showed more coccus shaped cells at the surface of nano-starch capsules. The cells encapsulated in starch nano-particles showed no or less viability upon their transit through SGID conditions, whereas native starch released cells slowly with 5.03 log CFU/g reaching intestinal phase. Starch nano-particles could not offer thermal protection to cells at high temperature-high time treatment. Further, free cells did not retain their bioactivity under SGID conditions, however enhanced bioactivity was observed upon encapsulation. The results indicate that starch nano-particles may not be suitable for encapsulation of probiotics. Highlights: Novel starch based nano-particles were used for encapsulating probiotic bacteria. Encapsulation in native starch showed better cells viability and thermal protection. Nano-encapsulated probiotic cells displayed lower viability compared to cells in native starch. Nano-starch particles could not offer thermal protection to probiotics cells. Nano-sized molecules may not suitable for encapsulation of probiotics.